Functional Genes and Bacterial Communities During Organohalide Respiration of Chloroethenes in Microcosms of Multi-Contaminated Groundwater - Hermon, Louis; Hellal, Jennifer; Denonfoux, Jérémie; Vuilleumier, Stéphane; Imfeld, Gwenaël; Urien, Charlotte; Ferreira, Stéphanie; Joulian, Catherine (Frontiers in Microbiology, 2019)
Microcosm experiments with CE-contaminated groundwater from a former industrial site were set-up to evaluate the relationships between CE biodegradation, dehalogenase genes and bacterial genera associated with CE biodegradation. Complete or partial dechlorination of PCE, TCE, cis-DCE and VC were observed independantly of the addition of reducing agent (Na2S) or electron donor (acetate). qPCR analysis of reductive dehalogenases genes (pceA, tceA, vcrA, and bvcA) revealed that the version of pceA gene found in the genus Dehalococcoides (hereafter named pceA(Dhc)) and vcrA gene increased in abundance by one order of magnitude during the first ten days of incubation. The version of the pceA gene found in the genus Dehalobacter (hereafter named pceA(Dhb)) and bvcA gene showed very low abundance and the tceA gene was not detected throughout the experiment. The proportion of pceA(Dhc) or vcrA relative to the universal 16S ribosomal RNA (16S rRNA) gene increased by up to 6-fold upon completion of cis-DCE degradation. Sequencing of 16S rRNA gene amplicons indicated that the abundance of dehalogenating genera Dehalococcoides, Sulforospirillum, and Geobacter was >20% relative abundance among total bacterial community in the microcosms. Among genera associated with dehalogenation , only the abundance of Dehalococcoides spp. increased up to 4-fold upon complete degradation of PCE and cis-DCE, suggesting a major implication of Dehalococcoides in the degradation of CEs. The relative abundance of pceA and vcrA genes correlated with the occurrence of Dehalococcoides and with degradation extent of PCE, cis-DCE and CV. A new type of dehalogenating Dehalococcoides sp. strain affiliated to the Pinellas group and suggested to contain both pceA(Dhc) and vcrA genes and may be involved in degradation of CEs in groundwater of the study site. Taken together, results demonstrated the in situ dechlorination potential of CE in contaminant plume groundwater, and suggest that monitoring of the dynamics of taxonomic and functional biomarkers in laboratory microcosms of contaminated groundwater following pollutant exposure may help predict the feasibility of bioremediation strategies at contaminated industrial sites.